Electoral Abstention and Progressive Governments in Latin America: Nicaragua and Venezuela - González Cortés, Wilson René (DIXI, 2014)
This article aims to present the changes and continuities in electoral abstention, starting from the eruption of governments with leftist tendencies in Latin America. Since the early 1990s, a series of governments have been elected in Latin America as alternatives to traditional politics, among which only Nicaragua and Venezuela conserve voting as a right rather than a duty or obligation. We believe that elections are a mechanism that enables verification of the level of legitimacy of these governments, so that abstention levels make it possible to determine to what extent those new policies foster the creation of more stable democracies. Taking a general approach to the role of legitimacy in the political system, we will look atthe role of elections in bourgeois liberal democratic systems. We will examine the character of so-called alternative governments along with the evolution of the abstentionist phenomenon in the two abovementioned countries. Their electoral abstention figures since the early 1980s show diverse trends worthy of consideration when characterizing their respective governments.
Keywords: abstentionism; alternative; elections; legitimacy.